2011
DOI: 10.1002/wsb.87
|View full text |Cite
|
Sign up to set email alerts
|

Grassland bird nest ecology and survival in upland habitat buffers near wooded edges

Abstract: Upland habitat buffers (i.e., strips of noncrop, herbaceous vegetation) that are established adjacent to wooded fencerows offer landowners an economical option to provide wildlife benefits within intensive agricultural landscapes. However, being located near a wooded edge may increase grassland bird vulnerability to edge effects through reduced nest survival. We examined nesting bird communities in field margins adjacent to wooded field edges with no buffer (i.e., control), narrow (approx. 10-m) buffers, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(46 reference statements)
2
4
1
Order By: Relevance
“…proximity to edge). Period survival estimates were lower than previous research on Dickcissels in the region based on structured searches in Clay County, Mississippi (27.9%; Adams et al 2013), and the Mississippi Alluvial Valley (12.9% and 19.1%; Conover et al 2011). However, Conover et al (2011 derived estimates based on a 20-day nesting cycle, and the initiation dates used for both studies were earlier than our data, which could account for differences in survival estimates.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…proximity to edge). Period survival estimates were lower than previous research on Dickcissels in the region based on structured searches in Clay County, Mississippi (27.9%; Adams et al 2013), and the Mississippi Alluvial Valley (12.9% and 19.1%; Conover et al 2011). However, Conover et al (2011 derived estimates based on a 20-day nesting cycle, and the initiation dates used for both studies were earlier than our data, which could account for differences in survival estimates.…”
Section: Discussioncontrasting
confidence: 67%
“…Commonly, nests are constructed by females in dense grass, forbs, or low woody vegetation, usually with overhead vegetative cover (Blankspoor 1970, Temple 2002. Dickcissels are a good model species to compare nest survey methods for grassland birds because previous research on this species has successfully located nests with all three search methods (Jensen & Finck 2004, Conover et al 2011, Sousa 2012.…”
Section: Study Systemmentioning
confidence: 99%
“…Snakes may be attracted to nest sites by activity of adults and nestlings (Stake et al ), and although the handling of nestlings agitated adults during our study, we strived to minimize the duration of our banding visits and did not infer predation of nests from snakes after banding (i.e., nest found empty and intact prior to the earliest potential fledge date; Thompson and Burhans ). Finally, the overall nest predation rate observed in our study (73.8%, or 83.6% when including fire ants) was at the middle‐ to lower end of the range reported in other dickcissel studies (range = 76–94% [Churchwell et al ; Conover et al , ]), and this may have reduced the effects of observers on nest predation relative to other studies.…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, nest site characteristics could influence nest survival rates (Martin et al ), which may potentially confound testing of observer effects in our study. For dickcissels, these include nest height (Conover et al ), grass coverage, and vegetation density (Winter , Conover et al ). To assess nests for these potential confounding variables, we measured nest‐site vegetation after nesting attempts were completed, including nest height measured from the ground to the base of each cup, grass coverage averaged from five 0.25‐m 2 frames (Daubenmire ) positioned around each nest (Winter ), and visual obstruction measured with a Robel pole (Robel et al ) at nest sites.…”
Section: Methodsmentioning
confidence: 99%
“…). Conover, Burger & Lindner () showed that field buffers increased nesting activities along field margins for a range of birds, including indigo buntings. In contrast, Riddle & Moorman () showed that implementing field borders had no beneficial effect on nesting success of indigo buntings.…”
Section: Discussionmentioning
confidence: 99%